Production of Biofuels and Chemicals with Bifunctional Catalysts - Fang, Zhen ; Smith., Richard L. ; Li, Hu (Springer, 2020)
Part I Fundamentals. Part II Bifunctional Chemocatalysis. Part III Production of Biodiesel